BECOMING THE MAY QUEEN: THE IMAGINARY, THE SYMBOLIC, AND THE REAL IN ARI ASTER’S MIDSOMMAR FILM - M. Zia Al Haromain; M. Naufal Abqory (Saksama: Jurnal Sastra, 2025)
This article explores Ari Aster’s Midsommar (2019) through a Lacanian psychoanalytic lens, focusing on the protagonist Dani’s psychological transformation as she navigates trauma, desire, and identity within the framework of Lacan’s tripartite register: the Imaginary, the Symbolic, and the Real. The film, positioned within the realm of popular horror cinema, offers a fertile text for examining how contemporary narratives ritualize and aestheticize psychological breakdowns. Dani’s disintegration following personal loss is restructured through her encounter with the Harga community, which functions as a symbolic order offering both the illusion of belonging and a mechanism of sublimation. Her final acceptance as the May Queen signifies not merely empowerment, but a complex negotiation between desire, repression, and the Other. Through this reading, Midsommar emerges as a modern cultural artifact that stages psychic trauma within the structures of popular visual culture, revealing the entanglements between horror, identity, and symbolic violence.